Cooperative Learning as a Means to Developing Students’ Critical and Creative Thinking Skills - Vijayaratnam, Phawani (INTI University College, 2009)
With the emphasis today on the employability of graduates, the debate is on whether classroom practices have much relevance to the ‘real world’. At higher education, as universities are the final pit stop for students before they embark to working lire, we, the educators, must be mindful of the demands of the workforce. This research will focus on how effective cooperative learning skills and the deliberate and conscious use of problem solving tools can aid students to develop their thinking skills which in turn can positively affect their personal, interactive and analytical skills - skills vital in the workforce. In this paper the researcher would like to define critical thinking as encompassing both logical and lateral thinking. It cannot be denied that both critical and creative thinking are interrelated and complementary aspects of thinking. Therefore, in order to develop effective thinking skills, one must pay attention to the development of both aspects of thinking. Feedback will be gotten from students via semester end compulsory student journals. Apart from that, observations, on the part of the instructor, will also be noted from time to time.